Development of high value food products from byproducts of the corn industry - Lee, Choon Min (2017)
Corn is one of the important food commodities in the world. When the corn reaches maturity, the edible part for consumption is only around 60% and approximately 40% of the corncob becomes wastage. Generally, the corncobs are either thrown, burnt or used as low-value products. There isn’t much report available on the use of these corncob wastes in food production for human nutrition. The main objective of this project is to develop high value food products (bread and instant cereal drink) which are high in dietary fiber by imparting low value corncob. Corncob and cornsilk were processed into powder with 80 microns mesh size. They were characterized in terms of nutritional values prior to further production of food products. Besides, cornsilk powder was extracted and characterized for its total flavonoid content with enyzme-assisted extraction method as well due to its reported high total flavonoid contents. Different batches of instant cereal drink and bread with different composition of corncob powder were formulated and produced. Effects of corncob powder composition on physicochemical properties and sensory acceptance of instant cereal drink and bread were investigated. Physicochemical properties such as viscosity, colour, specific volume, texture of these products were examined in this study. Sensory evaluation on the acceptance of these products involved several attributes was conducted as well. Different composition of corncob powder significantly affected the physicochemical properties and sensory acceptance of these products. Corncob powder had 38.39g dietary fiber, 43.59g carbohydrate, 3.24g protein, 1.4g fat, 11.51g moisture, 1.89g ash and calorie content of 199.83kcal/100g. For cornsilk, it had 6.01g dietary fiber, 71.26g carbohydrate, 2.91g protein, 0.02g fat, 18.18g moisture, 1.62g ash and calorie content of 296.84kcal/100g. As in the characterization of total flavonoid content in cornsilk powder, Pectinex Ultra SP-L was the best enzyme to aid the total flavonoids extraction from cornsilk powder. At the optimized condition, it increased the extraction yield for 125% compared to untreated control. Instant cereal drink with the addition of 30% corncob powder and bread with the addition of 10% corncob powder have the highest score of overall acceptance which are 6.00 and 7.00, respectively and were significantly different (p<0.05) with the other batches. This study showed that corncob powder can be imparted into food products to increase their nutritional value and at the same time, problem of waste from the corn industry can be reduced as well.